Bandgap modulation of ZnO/ZnS heterostructures through ion exchange and their efficient transport properties. (February 2022) - Qiao, Fen; Sun, Kaiyue; Liu, Wenjie; Xie, Yi; Chu, Huaqiang
Abstract: ZnO/ZnS heterojunction structures were grown through hydrothermal and anion exchanged method. The composition content and band gap of the composite were controlled by adjusting the sulfurization time. The surface morphology and crystal structure of prepared samples were investigated through SEM, EDS, TEM and XRD. It was found that ZnS coated the ZnO NRs and the smooth ZnO NRs became rough. In addition to the reduction of the ZnO/ZnS band gap due to the shell of ZnS, the formation of ZnO/ZnS heterogeneous structures can also improve the interface charge transport capability. ZnO/ZnS heterojunction structures with different sulfurization treatments all showed better hydrogen production performance compared with the pure ZnO. ZnO/ZnS with various sulfurization degrees were obtained by changing the sulfurization time of ZnO NRs. When the sulfurization time was 3 h, and the hydrogen production of ZnO/ZnS reached 2565.42 μmol g −1 (6 h). This strategy provides more favorable guidance for further fine regulation of heterojunction structure and functional applications. Highlights: Rod-shaped ZnO/ZnS heterojunction structures were prepared through hydrothermal and anion exchange approach. The band gap of ZnO/ZnS core-shell NRs became narrower in comparison to ZnO. The enhanced photocatalytic performance of ZnO/ZnS was obtained.